Lipid accumulation product index is inversely U-shaped associated with abdominal aortic calcification based on NHANES 2013–2014 - Deng, Jiangbei; Qin, Xiao (Frontiers in Cardiovascular Medicine, 2025)
BackgroundIn this study, we explored the correlation between lipid accumulation product (LAP) and abdominal aortic calcification (AAC).MethodsData collected from 2013–2014 were obtained from the National Health and Nutrition Examination Survey (NHANES) database. We utilized weighted univariate and multivariate regression analyses to assess the correlation between ln-LAP (LAP was transformed using a natural logarithm) and AAC. Further, subgroup analyses, smoothed curve fitting, and sensitivity analysis were implemented.ResultsThe study included 2,965 participants, with a mean ln-LAP index of 3.95 ± 0.83. Following adjustment for all covariates, multiple regression analyses indicated that ln-LAP, when modeled as a quadratic categorical variable, was significantly positively associated with AAC in Q3 (OR = 1.91; 95% CI: 1.20, 3.04, P < 0.001) compared to the Q1, and similarly, with severe abdominal aortic calcification (SAAC) in Q4 (OR = 2.17; 95% CI: 1.08, 4.35, P < 0.05). Conversely, Q2, Q3, and Q4 did not exhibit significant positive correlations with AAC scores (P > 0.05). Smoothed curve fitting revealed a nonlinear relationship between ln-LAP and AAC, characterized by an inverse U-shaped curve. Threshold effect analysis identified an inflection point at 4.21. Before this point, a marked positive correlation existed between ln-LAP and AAC (OR=1.74); beyond this point, a pronounced negative correlation was observed (OR=0.60). Subgroup analyses revealed no significant interactions regarding the correlation across age, sex, hypertension, and diabetes groups (P interaction >0.05).ConclusionsThis research reveals a significant inverse U-shaped correlation between LAP and the prevalence of AAC, implying that LAP could serve as a potential biomarker for evaluating AAC risk.